Canadian Cookbooks (1825–1949): In the Heart of the Home - Driver, Elizabeth (Petits Propos Culinaires, 2003)
This piece was given as one of the Savoir Faire lecture series at the National Library of Canada, Ottawa in January 2002. Very slight changes have been made as adjustment from the spoken to the written word. The article concerns how the author set about researching and compiling a major bibliographic reference tool documenting Canadian cookbooks dating from between 1825 and 1949.